Digital Payment Intention among Clean Agricultural Product Household Businesses in Vietnam’s Mekong Delta - Quang Nguyen Phuong; Nennie Trianna Binti Rosli; Aravindan Logeiswaran (Research Synergy Foundation, 2026)
Digital transformation has accelerated the adoption of digital payment systems across commercial sectors, including transactions involving clean agricultural products. However, the factors associated with the intention of household businesses to adopt digital payments remain poorly understood, particularly in developing agricultural economies. This study examines the factors influencing the intention of household businesses to choose digital payments for clean agricultural product transactions in Vietnam’s Mekong Delta. Quantitative research design was employed using survey data from 290 household businesses, and the proposed model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that trust is the strongest positive predictor of digital payment intention, followed by perceived usefulness and customer demand. In contrast, social influence has a statistically significant negative relationship with digital payment intention, contrary to the hypothesized positive direction. These findings indicate that confidence in payment systems, perceived functional benefits, and customer-driven market pressure are important in encouraging digital payment adoption, whereas prevailing social norms may constrain adoption in the study context. This study contributes empirical evidence to the digital payment literature by distinguishing market-driven customer demand from community-based social influence in explaining household businesses’ adoption of clean agricultural product transactions. The findings also provide practical implications for strengthening trust, communicating the functional benefits of digital payments, and addressing contextual barriers to digital transformation in the agricultural sector.